Pengaruh Return On Equity (ROE), Earning Per Share (EPS), Debt To Equity Ratio (DER) dan Return On Asset (ROA) terhadap Price To Book Value (PBV) pada Sektor Properti yang Terdaftar di Bei Periode 2019-2022 - Yustika Mulyasetiyani; Ahmad Idris; Karari Budi Prasasti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to determine the effect of ROE, EPS, DER, and ROA on PBV. This type of research is quantitative research. The data for this study were obtained through secondary data. The population in this study were all property companies listed on the IDX for the 2019-2022 period. The sample in this study was 44 financial reports with the sampling technique using purposive sampling. Data analysis technique using eviews. The results of the study showed that the partial t-test results of the ROE and EPS variables had an effect on PBV with a significance value of less than 0.05. The DER and ROA variables had a negative effect on PBV with a significance value greater than 0.05. The results of the simultaneous F-test of ROE, EPS, DER, and ROA on PBV had a positive and significant effect with a significance value less than 0.05.